Insight Into the Nuclear and Mitochondrial Genome of the Caribbean King Crab Maguimithrax spinosissimus (Crustacea: Brachyura: Mithracidae) to Support Fisheries Management and Conservation Initiatives - Juan Antonio Baeza (Ecology and Evolution, 2025)
ABSTRACT The Caribbean King crab Maguimithrax spinosissimus is the largest brachyuran in the western Atlantic and target of subsistence, recreational, and/or artisanal fisheries. Also, its abbreviated larval period makes it a candidate for mariculture to support coral reef restoration efforts. In this study, I benefitted from a series of bioinformatics tools tailored for low‐sequencing‐depth next generation datasets that allow to gain insight into the genome of a species. K‐mer profiling indicated a haploid genome size that ranged between 2.16 Gbp (k‐mer = 51) and 2.63 Gbp (k‐mer = 21). At least one half and a maximum of three fourths of the nuclear genome comprised mobile elements. Just over one half (57.49%) of the repetitive elements in the nuclear genome of the Caribbean King Crab were not annotated. If only annotated mobile elements are taken into account, the most common were classified as Long Interspersed Nuclear Elements (29.18%). Much less common transposable elements included DNA transposons (5.63%), Long Terminal Repeats (2.69%), and Rolling Circles (1.93%). The mitogenome of the Caribbean King Crab was 15,714 bp long and encoded for 13 protein‐coding genes, 22 transfer RNA genes, and two ribosomal RNA genes. A maximum likelihood phylogenetic analysis based on translated PCGs supported the monophyletic status of the superfamily Majoidea and family Mithracidae but not the Majidae. The results from this study will help adjusting resources optimally to assemble a chromosome‐level nuclear genome in the Caribbean King crab. The assembled mitogenome is expected to support biomonitoring of this species in coral reefs using environmental DNA. Overall, the developed genomic resources can be used to support conservation planning and fisheries regulation in M. spinosissimus, the largest crab in the Caribbean basin with potential for aquaculture to support coral reef restoration.